Representationof lesbianity inthe maranhensenovel Uma sombrana parede, by Josué Montello (Revista Crioula, 2022)
The paper analyzed the lesbianism in the maranhense novel Uma Sombra na Parede(1995), by Josué Montello. The research was bibliographic, exploratory and explanatory. It was basedon Beauvoir (1980), Foucault (2007) and others. Therefore, the narrator demonstrated, in the novel,the ultra-conservative view with which maranhense society perceived lesbian women, based ondiscourses of power and control over bodies, including the biblical/religious.